Method for determining the thickness of a binder layer at its non-uniform mass transfer inside the channel of a honeycomb filler made from polymeric paper - Kondratiev, Andrii; Slivinsky, Michael (Eastern-European Journal of Enterprise Technologies, 2018)
Sandwich panels with honeycomb filler based on polymer paper "Nomex" is widely used in crucial structures for various purposes. In the process of manufacturing such panels, some factors of the technological process, such as the application of the binder on a honeycomb filler, the temperature modes of drying and polymerization of the applied layer, most significantly affect physical-mechanical characteristics of finished products. A specific factor of production of a honeycomb filler from polymer paper is its multi-stage impregnation with the dressing composition, and then by the binder during the final operations with subsequent drying and heat treatment of the honeycomb units. These operations result into non-uniform heat and mass transfer (migration) of the binder from the central part of the panel to its peripheral end areas. The regularities of this non-uniform heat and mass transfer of the binder along the length of a honeycomb channel were explored. It was shown that these phenomena are conditioned by hydrodynamic motion of the binder, caused by temperature gradient, its density and surface tension coefficient. Based on this, we designed the method for determining the thickness of the binder layer along honeycomb channels at the known (assigned) law of the change in density and surface tension along the length of the cell of a honeycomb filler. The method makes it possible to reduce the non-uniformity of mass transfer by technological means, ensuring the necessary tolerance for physical-mechanical characteristics of honeycomb fillers from polymer paper. The problem of mass transfer enabled deeper revealing the mechanisms of the formation of the non-uniform impregnation layer at the stages of the drying process during the production of a honeycomb filler from polymer paper. Using the obtained mechanisms and technological possibilities of the regulation of characteristics of binders, it is possible to improve the non-uniformity of the layer thickness along the honeycomb channels to the values that ensure the necessary tolerance for physical-mechanical characteristics of a honeycomb filler